MANAGEMENT FAMILY COMMUNICATION PATTERNS OF FEMALE TEACHERS AT STATE SECONDARY SCHOOL WEST JAVA - Deden Ramdan (Jurnal Riset Bisnis dan Manajemen, 2022)
This study entitled “Family Communication Patterns Of Female Teachers At State Secondary School 15 Bandung City District West Java Province”. Female teachers who become informants are those whor are married and have children. The purpose of this study was to find out how or the pattern of communication carried out by a female teachers in childcare. And which family communication pattern will they use in parenting. The method used in this study is a qualitative research method with the theory of family communication pattern. With qualitative methods, researchers can obtain data using in-depth interview techniques so that the it is hoped that the data obtained will be able to complement and produce comprehensive qualitative descriptive data. The results obtained from this study are the communication patters that exist between female teachers and their families, where a pluralistic pattern is chosen from the four patterns contained in the concept of family communication, as a result of this entire research.